Water storage module - PAN SHUJUN (2017)
The utility model belongs to the technical field of tank or the technique of pond construction of infiltrating and specifically relates to a water storage module is related to. The utility model provides a water storage module includes the water storage unit, the water storage unit includes first stand, second stand, post edge and connecting rod, first stand with the one end of second stand all is provided with the post and follows, first stand is the cylinder, the second stand is the square column, it is a plurality of first stand one -tenth matrix arrangement, it is a plurality of the second stand sets up the matrix that first stand formed is peripheral, and with first stand forms the matrix jointly, adjacent two the post passes through between following the connecting rod is connected. The utility model provides a water storage module sets up first stand into the cylinder, sets up the second stand into the square column cooperation of the stand through the different grade type for the compressive capacity